A Green Solvent Processable Wide‐Bandgap Conjugated Polymer for Organic Solar Cells. Issue 12 (26th October 2020) - Lu, Hao; Jiang, Pengcheng; Wei, Yaoyao; Yuan, Shiling; Liu, Yahui; Li, Wenhua; Xu, Xinjun; Bo, Zhishan
Abstract : Herein, a novel wide‐band‐gap donor polymer, PBTVT, which comprises a bis(carboxylic ester)‐substituted thiophene–vinylene–thiophene (TVT) acceptor unit and benzodithiophene donor unit, is designed and synthesized. PBTVT displays good solubility in halogen‐free green solvents such as o ‐xylene at elevated temperature. Grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) measurement revealed that PBTVT can form the desired face‐on orientation in the blend films. Organic solar cells are fabricated with PBTVT as the donor and ITOIC‐2F as the acceptor. Although the highest occupied molecular orbital (HOMO) level offset between PBTVT and 2, 2′‐((2Z, 2′Z)‐(((4, 4, 9, 9‐tetrakis(4‐hexylphenyl)‐4, 9‐dihydro‐ s ‐indaceno[1, 2‐b:5, 6‐b′]dithiophene‐2, 7‐diyl)bis(3, 4‐bis(hexyloxy)thiophene‐5, 2‐diyl))bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1H‐indene‐2, 1‐diylidene))dimalononitrile (ITOIC‐2F) is only 0.08 eV, devices still exhibit an overall power conversion efficiency (PCE) of 11.04%. Especially, devices fabricated with the green solvent o ‐xylene outperform those fabricated with halogenated solvents such as 1, 2‐dichlorobenzene ( o ‐DCB). Abstract : A novel donor polymer PBTVT comprising a bis(carboxylic ester)‐substituted thiophene–vinylene–thiophene acceptor unit and a benzodithiophene donor unit is designed and synthesized. It displays a wide bandgap of 1.87 eV and good solubility in halogen‐free solvents such as o ‐xylene. The corresponding devices exhibit a high PCE of 11.04%, though the highest occupied molecular orbital (HOMO) level offset is small (0.08 eV).